Vocabulary lists vs. contextualized teaching of vocabulary: the question of retrieval, recall and use in written productions at colleges of education - Masciotra, Romina (2011)
During decades, there has been growing interest in the realm of English Language Teaching (ELT) in connection to vocabulary learning and teaching. Some authors have shown that this concern was sometimes related to the influence these processes may have on students’ written productions and the learning of another language. The purpose of the present study is to address the following query: To what extent lexical items are taught through vocabulary lists or incidentally derived from context in Colleges of Education in the City of Buenos Aires and what effect do these two vocabulary teaching methods have on future retrieval, recall and instances of actual use in students’ written productions. Qualitative research was carried out in order to fully understand this phenomenon. In addition, quantitative techniques were implemented because they contributed to the understanding of the issue. In order to collect the data, a group of English Language teachers at Colleges of Education were interviewed, students attending the same Colleges of Education in which the teachers mentioned above teach English Language I were also surveyed, and samples of written productions by these students collected through a random sampling technique were also analyzed. Research results have shown that teachers agree that vocabulary should be given as part of a context, not in isolation. According to the teachers, this will help students build up the meaning of the items and better understand their collocations, the register in which they should be used, among others, but especially it will help them learn how to use the new vocabulary in their productions.